Is voting for young people? - Wattenberg, Martin P., 1956- (Great questions in politics series, 2007)
The aging of regular newspaper readers -- The aging audience for politics on TV -- Don't ask anyone under 30 -- Where have all the young voters gone? -- Do young adults see voting as a civic duty? -- Does low youth turnout really matter? -- What can be done?